Comparative analysis of serum lipid profiles in patients with and without gallstones: A prospective cross-sectional study. (June 2019) - Hayat, Sikandar; Hassan, Zarbakht; Changazi, Shabbar Hussain; Zahra, Anam; Noman, Muhammad; Zain ul Abdin, Muhammad; Javed, Haris; Ans, Armghan Haider
Abstract: Objectives: Gallbladder disease is one of the most common diseases of the gastrointestinal tract. Various studies have shown an association between gallstones and an alteration in the serum lipids. The objective of this study was to compare serum lipid profile of gallstone patients with the controls. Methods: This prospective cross-sectional study was conducted in the Surgical Department of the Services Institute of Medical Sciences from August 2017 to August 2018. A total of 50 patients were included in the study after screening through the inclusion criteria. A control group of 50 inpatients with no personal or family history of gallstones were also recruited for comparison. Results were expressed as mean with standard deviation. Students t-test was used to compare the data between the patients and the control groups (p < 0.05 was considered statistically significant). SPSS software, version 20 was used for statistical analysis. Results: The mean age of the patients was 40.90 years and that of controls was 34.74 years. 46 patients were females and 44 controls were females. The serum cholesterol levels were high in the patients as compared to the controls but the comparison was not statistically significant. Serum triglycerides levels were high in the patients as compared to the controls and the analysis was statistically significant. Furthermore, the serum HDL levels were low in the patients as compared to the controls with a statistically significant p-value. However, the serum LDL levels were low in the patients as compared to the control group. Conclusion: It was concluded that serum triglyceride levels and serum HDL levels were statistically significant in gallstone patients and there was a positive correlation between these parameters and gallstone disease. Highlights: Gallbladder disease is one of the most common diseases of the gastrointestinal tract in Pakistan. Various studies have shown an association between gallstones and an alteration in the serum lipids. This study was conducted to find out the association of dyslipidemias with formation of gallstones. Serum lipid profile of gallstones patient was compared with inpatient control group. It was concluded in study that serum triglyceride levels and serum HDL levels were statistically significant in gallstone patients and there was a positive correlation between these parameters and gallstone disease.